Does Servant Leadership Stimulate Work Engagement? The Moderating Role of Trust in the Leader - Zhou, Guangya; Gul, Rani; Tufail, Muhammad (Frontiers in Psychology, 2022)
A positive leadership style can promote work engagement. Using social exchange theory, this study examines the impact of employee leadership styles on work engagement. In addition, the link also considered the mitigating role of trust in leaders. Preliminary data was collected from the educational and non-educational staff of the Business Management Sciences and Education Department at different universities. We collected responses from 242 employees from selected universities using the purposive sampling technique. We tested the proposed hypothesis using linear regression. Research has shown that there is a positive link between employee leadership and work engagement. When trust in leaders as facilitators was introduced, the relationship between leadership and work engagement was relaxed to increase trust in leaders. Practical and theoretical contributions to the study were provided with recommendations for further study.